Applying Brown and Levinson’s model to investigate the differences in the use of politeness strategies between spoken Saudi and British English - Alqahtani, Hanaa (Research Journal in Advanced Humanities, 2024)
The aim of the study was to apply Brown and Levinson’s model of politeness to investigate the differences in the female use of politeness strategies between spoken Saudi and British English. The study applied an observation approach and consisted of 103 female participants which were divided into 2 groups. The 1st group comprised of 53 native speakers of Saudi Arabia and the other one consisted of 50 British English females. The researcher met the participants to explain that they would be given 15 real-life situations and they had to carefully listen to each one of them and respond. These situations were designed by the researcher according to Brown and Levinson’s (1987) contextual determinants. The researcher noted their response to every situation on a pre-designed evaluation sheet. The data collected was quantitatively analyzed using SPSS program to test the significant differences between Saudi and British groups in the types of politeness strategies and the realization of the contextual determinants based on the frequencies. The findings of the study reflected significant inter-group differences in the realization of some of the contextual determinants but power did not have an influence on the speakers’ performance of polite offers in both the cultures, and for social distance the result showed significant influence on the British use of politeness strategies. In conclusion, the study findings supported Brown and Levinson (1987) politeness theory in terms of cross-cultural similarities and differences.